The force of character and the lasting life - Hillman, James (Random House, 1999)
"The Force of Character presents a new thesis: The changes of old age, even the debilitating ones, have purposes and values organized by the psyche. Memory for recent events may falter, offering more place for long-term recollections. A heart condition in later life brings an opportunity to remove blockages from constricted relationships, while changes in sleep patterns allow the old to experience the profound elements of nighttime that we usually overlook. As Hillman says, "Aging makes metaphors of biology."" "James Hillman resurrects the ancient, widespread, and socially effective idea of the old person as "ancestor," a model for the young, the bearer of a society's cultural memory and traditions."--BOOK JACKET.